2021
DOI: 10.3390/cells10071706
|View full text |Cite
|
Sign up to set email alerts
|

The Role of miRNAs in Extracellular Matrix Repair and Chronic Fibrotic Lung Diseases

Abstract: The lung extracellular matrix (ECM) plays a key role in the normal architecture of the lung, from embryonic lung development to mechanical stability and elastic recoil of the breathing adult lung. The lung ECM can modulate the biophysical environment of cells through ECM stiffness, porosity, topography and insolubility. In a reciprocal interaction, lung ECM dynamics result from the synthesis, degradation and organization of ECM components by the surrounding structural and immune cells. Repeated lung injury and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 179 publications
(196 reference statements)
1
10
0
Order By: Relevance
“…In addition, we recognize that subjects with asthma were not age matched to the control or IPF subjects. The decreased expression of miR-34a and -199, fibrotic inducing microRNAs highlight the differences in cargo content between exosomes from various lung diseases supporting future investigations (Usman, Hsieh, & Hackett, 2021;Weidner et al, 2021).…”
Section: Discussionsupporting
confidence: 55%
“…In addition, we recognize that subjects with asthma were not age matched to the control or IPF subjects. The decreased expression of miR-34a and -199, fibrotic inducing microRNAs highlight the differences in cargo content between exosomes from various lung diseases supporting future investigations (Usman, Hsieh, & Hackett, 2021;Weidner et al, 2021).…”
Section: Discussionsupporting
confidence: 55%
“…Deregulation of miRNAs translates into altered expression of molecules and subsequent alteration in the pathways involved. Differences in the expression of miRNAs involved in the remodeling of the extracellular matrix have been reported in several chronic lung diseases [ 36 ], and in particular, an increase has been shown in the levels of miR-15b in lung tissue from COPD patients, which correlates with disease severity [ 37 ], whereas a decrease was observed in miR-145-5p [ 23 ] and miR-181c [ 38 ]. The Hippo signaling pathway is a master regulator of ECM processes in lung development and disease [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Until now, it has been demonstrated that human miRNAs listed in public databases represent only a small fraction of the total human miRNA repertoire [ 38 , 40 , 175 ]; therefore, it is necessary to update these studies to improve our understanding about the complex gene expression regulation network in diseases such as IPF. Some studies have estimated that approximately 60% of the human coding transcripts are regulated by miRNAs [ 38 , 125 , 176 ]. Moreover, recent reports indicate that an important number of miRNAs are associated with the TGF-β-dependent Smad and non-Smad dependent signaling pathway, with the EMT activation process, and with the consequent fibroblast activation and myofibroblast differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the search, analysis, and discussion of new treatment options are necessary. Among these new options are the miRNAs because of their role as regulators of signaling pathways and cell functionality, which suggests that they probably play a role in this pathology [ 124 , 125 ]. The most recent information on dysregulated miRNAs implicated in the pathophysiology of IPF is depicted in the Table 1 .…”
Section: Non-smad-dependent Signaling Pathways In Emt Induced By Tgfβmentioning
confidence: 99%